2009
DOI: 10.1007/s10528-009-9276-9
|View full text |Cite
|
Sign up to set email alerts
|

Two Different Size Classes of 5S rDNA Units Coexisting in the Same Tandem Array in the Razor Clam Ensis macha: Is This Region Suitable for Phylogeographic Studies?

Abstract: For a study of 5S ribosomal genes (rDNA) in the razor clam Ensis macha, the 5S rDNA region was amplified and sequenced. Two variants, so-called type I or short repeat (approximately 430 bp) and type II or long repeat (approximately 735 bp), appeared to be the main components of the 5S rDNA of this species. Their spacers differed markedly, both in length and nucleotide composition. The organization of the two variants was investigated by amplifying the genomic DNA with primers based on the sequence of the type … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
(47 reference statements)
1
3
0
Order By: Relevance
“…We could suppose that divergent NTSs are located at different arrays where they have evolved independently, but we have shown that some species (S. patula and E. cultellus) have divergent NTS organised in tandem. In the same way, a few clones containing a-and d-, and a-and g-NTSs were characterised in E. directus (Vierna et al, 2009), and other studies found an intermixed organisation of 5S rDNA variants in grey mullets and E. macha (Gornung et al, 2007;Fernández-Tajes and Méndez, 2009). These findings support the idea that 5S rDNA frequently moves on within genomes (see below).…”
Section: Discussionsupporting
confidence: 75%
“…We could suppose that divergent NTSs are located at different arrays where they have evolved independently, but we have shown that some species (S. patula and E. cultellus) have divergent NTS organised in tandem. In the same way, a few clones containing a-and d-, and a-and g-NTSs were characterised in E. directus (Vierna et al, 2009), and other studies found an intermixed organisation of 5S rDNA variants in grey mullets and E. macha (Gornung et al, 2007;Fernández-Tajes and Méndez, 2009). These findings support the idea that 5S rDNA frequently moves on within genomes (see below).…”
Section: Discussionsupporting
confidence: 75%
“…The length of the 5S units was about 275–300 bp for D. trunculus , about 450 bp for D. variegatus and around 500 bp for fragments obtained from the other two Donax species with minimal variation (1–12 bp) among clones (Table 2 ). Taking as reference the 5S rRNA sequences available in other bivalve species [ 9 , 17 , 25 , 26 , 44 , 55 ], the coding region was assigned to 120 bp in the four cases and the non-transcribed spacer (NTS) region to the remaining sequence (Table 2 ). BLASTn analysis corroborated the identity of the limited region and indicated that no other coding sequence was included in the 5S rDNA repeat unit.…”
Section: Resultsmentioning
confidence: 99%
“…But bivalve molluscs stand out for being one of the most extensively studied group of organisms regarding 5S rDNA and ITS region, showing high levels of gene organization as well as a vast diversity of gene arrangements. Molecular organization of ITS region and 5S rDNA has been studied in cockles [ 26 28 , 43 ], mussels [ 44 ], oysters [ 9 , 10 ], scallops [ 41 , 42 , 45 , 46 , 55 ], razor clams [ 25 , 99 , 100 ] and Veneroida clams [ 3 ], but it have never been studied in the wedge clams of the genus Donax .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of a multigene family subjected to effective concerted evolution, all the copies within a genome are expected to be identical and represented by the Sanger sequenced reference sequence. However, intragenomic sequence variation in multigene families is common in several eukaryotic lineages 19,69,[78][79][80] , and sometimes involves size variation 81,82 . In these cases, a Sanger sequence can be considered as a consensus of all the divergent copies of the amplified gene.…”
Section: Discussionmentioning
confidence: 99%